Gendered Matooke product profile in Uganda - Nowakunda, Kephas; Akankwasa, Kenneth; Khakasa, Elizabeth; Asasira, Moreen; Kisakye, Sarah; Arnaud, Elizabeth; Mukasa, Yusuf; Nuwamanya, Ephraim; Uwimana, Brigitte; Bugaud, Christophe; Dahdough, Layal; Bouniol, Alexandre; et al. (2022)
The WP1 Gendered Food Product Profile for Matooke in Uganda reflects the final step ( step 5) of an interdisciplinary five-step methodology developed to identify demand for quality characteristics among diverse user groups along the food chain ( Forsythe et al., 2022). This methodology includes: step 1) interdisciplinary state of knowledge of the product ; step 2) gendered food mapping, which includes participatory research with men and women in rural communities regarding their product preferences and priorities; step 3) participatory processing diagnosis and quality characteristics ; and step 4) consumer testing studies in rural and urban areas of the product using contrasted RTB varieties. Results from step 1 and 2 have been published in Kenneth Akankwasa, Pricilla Marimo, Robooni Tumuhimbise, Moreen Asasira, Elizabeth Khakasa, Innocent Mpirirwe, Uli Kleih, Lora Forsythe, Geneviève Fliedel, Dominique Dufour & Kephas Nowakunda (2021). The East African highland cooking bananas ‘Matooke’ preferences of farmers and traders: Implications for variety development. International Journal of Food science and Technology, 56(3), 1124-1134. https://doi.org/10.1111/ijfs.14813.